Oral health experiences of Turkish children with acute rheumatic fever or rheumatic heart disease - Aslı Soğukpınar Önsüren; Ufuk Utku Güllü; Sevcan İpek (European Oral Research)
Purpose: Children with acute rheumatic fever (ARF) or using depot-penicillin because of rheumatic heart disease (RHD) are prone to the risk of infective endocarditis (IE) and poor oral hygiene. This cross-sectional study aimed to investigate oral health experiences of a group of healthy children and a group of children with ARF or who were using depot-penicillin because of RHD (study group). Material and methods: Medical and dental data of 86 children aged between 5-12 years were investigated in this study. Medical histories, decayed, missing, and filled teeth, plaque index, gingival index, toothbrushing frequencies, and the study and healthy groups’ socioeconomic levels were recruited and examined. Results: The ‘dmft’ of the study and healthy groups were found to be 5.51 ± 3.81 and 2.37 ± 2.31, respectively, while the ‘DMFT’ of the study and healthy groups were 1.71 ± 2.28 and 1.06 ± 1.59, respectively. There was no significant difference between the gingival indexes of the study group 0.89 ± 0.39 and the healthy group 0.62 ± 1.03 (p=0.112). Nevertheless, the groups significantly differed regarding the plaque index, which were 0.87 ± 0.40 and 0.45 ± 0.41, respectively (p<0.001). The tooth brushing frequencies in the study and healthy groups being twice a day or more were 23.3% and 46.5%, respectively. Conclusion: The children with ARF or using depot-penicillin because of RHD had more permanent and primary tooth caries and poorer oral health than the healthy group in this study.